Building PulseNet Latin America and Caribbean Salmonella regional database: First conclusions of genetic subtypes of S. Typhi, S. Typhimurium and S. Enteritidis circulating in six countries of the region - Campos, Josefina (2012)
Fil: Campos, Josefina. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.